Pengaruh Brand Image dan Produk Knowledge Terhadap Purchase Intention Produk Workshop From Home di Top Coach Indonesia - Febi Rahmawati; Yayak Heriyanto (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to determine the effect of Brand Image and Product Knowledge on PurchaseIntention of Workshop products at Top Coach Indonesia. This research used quantitativeresearch methods with associative approach. The primary data was obtained fromquestionnaire distribution. The population of this study was 591 participants of Workshop fromHome at Top Coach Indonesia in April 2020 with a sample of 86 people. The analysis methodsused included validity, reliability, and normality tests; multiple linear regression; correlationcoefficient analysis; determination coefficient test; and hypothesis testing using SPSS. Theresults of this study indicate that: (1) Brand Image has a positive effect on Purchase Intentionwith a regression value of 0.566 and a significance level of 0.000; (2) Product Knowledge hasa positive effect on Purchase Intention with a regression value of 0.659 and a significance levelof 0.000; (3) Brand Image and Product Knowledge simultaneously have a positive effect onPurchase Intention with an Fcount value of 91.743, which is greater than Ftable of 3.11, and asignificance level of 0.000, which is less than 0.05; and (4) the influence of Brand Image andProduct Knowledge on Purchase Intention is 68.10% with the remaining 31.90% influenced byother variables not examined by the author.